2019
DOI: 10.1017/s0714980818000600
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provider Experiences of and Perspectives on Medical Assistance in Dying: A Scoping Review of Qualitative Studies

Abstract: RÉSUMÉUne grande partie des écrits sur l’aide médicale à mourir (AMM) qui traite de la perspective des prestataires de soins de santé est centrée sur le rôle des médecins, et le point de vue des infirmières n’est exprimé que dans quelques-uns d’entre eux. Toutefois, quelques provinces canadiennes ont mis en œuvre des approches multidisciplinaires pour l’AMM. Il serait donc important de mieux comprendre l’expérience des divers prestataires de soins de santé impliqués dans l’AMM, considérant que les plans provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…10 Other challenges included the emotional tensions experienced by palliative care physicians in the Netherlands and United States, including feelings of strain, loneliness, and being conflicted. 11 Similarly, Brooks 12 conducted a scoping review of qualitative literature and called for further investigation into the experiences of diverse MAiD providers in the Canadian setting. Reported findings specific to Dutch physician providers include studies that underline stressful, negative experiences of providing assisted dying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…10 Other challenges included the emotional tensions experienced by palliative care physicians in the Netherlands and United States, including feelings of strain, loneliness, and being conflicted. 11 Similarly, Brooks 12 conducted a scoping review of qualitative literature and called for further investigation into the experiences of diverse MAiD providers in the Canadian setting. Reported findings specific to Dutch physician providers include studies that underline stressful, negative experiences of providing assisted dying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 However, many have identified that the experiences of family members and HCPs of people who have been found eligible for, or have received, assisted dying need to be better understood and addressed in institutional policies and care plans. 1,3 6…”
Section: Experiences Of Family Members and Healthcare Providersmentioning
confidence: 99%
“…8 Similarly, HCPs’ involvement in the assisted dying process is often described to be psychologically and emotionally challenging. 3,5,8,9 Prescribing or administering medications that result in death typically fall under physicians’ scope of practice, with the exception of Canada, where nurse practitioners have the same privileges. 3 Other HCPs, including nurses, pharmacists/pharmacy technicians, social workers, and spiritual care practitioners, play vital roles in the assisted dying process.…”
Section: Experiences Of Family Members and Healthcare Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding relationship(s) between MAiD and palliative care, participants generally reinforced the need for relationships and communication in their provision as well as the importance of interprofessional roles and dynamics for patient-centred care at end of life. 33 Participants’ eagerness to see MAiD as a component of palliative care also echoed the need for an Action Plan in order to co-exist in this new landscape, 34 especially in view of the predicament for palliative patients to have to cease medications to remain compos mentis in order to meet current MAiD criteria.…”
Section: Discussionmentioning
confidence: 99%